Characterization of demographics and NS5A genetic diversity for hepatitis C virus genotype 4‐infected patients with or without cirrhosis treated with ombitasvir/paritaprevir/ritonavir. Issue 9 (8th May 2018) - Schnell, G.; Tripathi, R.; Beyer, J.; Reisch, T.; Krishnan, P.; Dekhtyar, T.; Irvin, M.; Hall, C.; Yu, Y.; Mobashery, N.; Redman, R.; Pilot‐Matias, T.; et al.
Summary: Hepatitis C virus (HCV) genotype 4 (GT4) is genetically diverse with 17 confirmed and 4 provisional subtypes. In this report, HCV GT4‐infected patient samples from Phase 2/3 clinical studies were analysed to characterize global demographics and genetic diversity of GT4 infection among patients treated with ombitasvir (OBV, NS5A inhibitor) plus paritaprevir/r (NS3/4A inhibitor codosed with ritonavir). Among 17 subtypes isolated from GT4‐infected patients in the PEARL‐I and AGATE‐I studies, subtype prevalence by country of enrolment and country of origin suggested that subtypes 4a and 4d were likely circulating in Europe, while heterogeneous GT4 subtypes and a portion of GT4a detected in European and North American countries were likely due to immigration of HCV‐infected patients from Africa. The distributions of birth cohort and race were also significantly different across GT4 subtypes 4a, 4d, and non‐4a/4d. In addition, phylogenetic analyses of NS5A sequences revealed clustering within subtype 4a which segregated by the patient‐reported country of origin and the presence of the L30R/S polymorphism. HCV NS5A sequences derived from GT4a‐infected patients who originated from Europe and the United States clustered separately from sequences derived from patients who originated from Egypt, suggesting that genetically distinct strains of subtype 4a may be circulating globally. Finally, NS5A baseline polymorphisms were frequently detected at amino acid positions of interest for the inhibitor‐class and OBV retained activity against 37 of 39 NS5A GT4 clinical isolates, with no impact on treatment outcome in the PEARL‐I and AGATE‐I studies.